Mercury Determination: A Hair Raising Experiment - Duford, David; Lafleur, Josiane P.; Lam, Rebecca; Skinner, Cameron D.; Salin, Eric D. (McGill Science Undergraduate Research Journal, 2006)
A novel, fast, low-cost portable system for the total analysis of mercury (Hg) in human hair is presented by induction heating-electrothermal vaporization, gold amalgamation, atomic absorption spectrometry (IH-ETV-GA-AAS). Using this innovative technique a detection limit of 1 ng (or 1.5 mg/g based on a 0.6 mg sample) was achieved.